2023
DOI: 10.15252/embj.2022112514
|View full text |Cite
|
Sign up to set email alerts
|

Blue light promotes zero‐valent sulfur production in a deep‐sea bacterium

Abstract: Increasing evidence has shown that light exists in a diverse range of deep-sea environments. We unexpectedly found that blue light is necessary to produce excess zero-valent sulfur (ZVS) in Erythrobacter flavus 21-3, a bacterium that has been recently isolated from a deep-sea cold seep. E. flavus 21-3 is able to convert thiosulfate to ZVS using a novel thiosulfate oxidation pathway comprising a thiosulfate dehydrogenase (TsdA) and a thiosulfohydrolase (SoxB). Using proteomic, bacterial two-hybrid and heterolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
5
1
Order By: Relevance
“…Remarkably, the thiosulfate group displayed a visible increase of the intracellular elemental sulfur compared to the control group on day 1 (Figure ). However, the relative expression levels of the sox or tsdA genes of no more than 2-fold upregulation during S 0 formation (Figure S6A) are inconsistent with the previous study . In addition, the genomic sequences indicated that T.…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…Remarkably, the thiosulfate group displayed a visible increase of the intracellular elemental sulfur compared to the control group on day 1 (Figure ). However, the relative expression levels of the sox or tsdA genes of no more than 2-fold upregulation during S 0 formation (Figure S6A) are inconsistent with the previous study . In addition, the genomic sequences indicated that T.…”
Section: Resultscontrasting
confidence: 83%
“…Currently, we cannot rule out the possible factors such as light or oxygen that initiates S 0 production in T. mangrovi. , In addition, T. mangrovi harbors the dsrABEFCHMKLJOP clusters encoding dissimilatory siroheme sulfite reductase and other proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being fundamental and providing a wider perspective, but not often explored yet is the role of cyclic di‐GMP signaling in biogeochemical cycling. Promotion of biofilm formation on sulfur and pyrite, iron disulfide, the regulation of cytochrome c‐type proteins on the transcriptional level, involvement in the regulation of the abiotic sulfur cycle, and enhanced biofilm formation by anaerobic, oceanic ecosystem relevant electron acceptors couples cyclic di‐GMP signaling to the global abiotic sulfur cycle and biogeochemical and ancient energy conservation processes (Cai et al, 2023; Martin‐Rodriguez et al, 2021; Ng et al, 2020; Ruiz et al, 2012). Whether cyclic di‐GMP signaling is involved to a larger extent in the global abiotic or biotic sulfur cycle equally as in the global nitrogen and carbon cycles remains to be shown.…”
Section: Role Of Cyclic Di‐gmp Signaling In Biogeochemical Cyclingmentioning
confidence: 99%
“…The presence of potential cyclic di-GMP turnover proteins in deepest branching bacteria indicates that cyclic di-GMP is an ancient signaling molecule. In this issue of The EMBO Journal, Cai et al (2023) B ioinformatic analyses pinpoint cyclic di-GMP as the most abundant second messenger in bacteria. Ubiquitously regulating the lifestyle transition between sessility and motility, this signaling molecule has been mainly investigated in animal and plant pathogens, where it not only regulates the trade-off between environmental survival versus acute virulence but also directs the intracellular lifestyle of microbes (Ro ¨mling et al, 2013).…”
mentioning
confidence: 99%